Pengetahuan Orangtua Mengenai Pendidikan Seksual Bagi Anak dengan Gangguan Spektrum - Kusumandari, Rahma (Persona:Jurnal Psikologi Indonesia, 2018)
Abstract - Parents play an important role in sexual education for their children. The role also owned by parents who have children with autism spectrum disorder (ASD). However, information about sexual education for children with ASD is limited. This condition caused parents feel confused about when and how to provide sexual education to their children who have ASD. This study aims to determine the level of parental knowledge about sexual education in children with ASD. The measuring instrument used in this study was a test of knowledge about sexual education in children with ASD. Respondents in this study involved 80 parents who had children with ASD in Surabaya. The results showed that 28% of respondents had a moderate level of knowledge regarding sexual education in children with ASD.  Nearly half or 48% of respondents have a good level of knowledge, and 15% of respondents have a lack of knowledge. Most parents have insufficient knowledge in terms of understanding sexuality, the stage of sexual development, and the topic of sexual education that is appropriate for the age of the children with ASD. Keywords: sexual education, parental knowledge, autism spectrum disorder Abstrak – Orangtua memegang peranan penting dalam pendidikan seksual bagi anaknya. Termasuk orangtua yang memiliki anak dengan gangguan spektrum autis (GSA). Akan tetapi, informasi tentang pendidikan seksual bagi anak dengan GSA ini terbatas. Kondisi tersebut mengakibatkan orangtua merasa bingung tentang kapan dan bagaimana memberikan pendidikan seksual pada anaknya yang memiliki GSA. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan orangtua tentang pendidikan seksual pada anak GSA. Alat ukur yang digunakan dalam penelitian ini adalah tes pengetahuan tentang pendidikan seksual pada anak GSA. Responden dalam penelitian ini adalah 80 orangtua yang memiliki anak GSA di Surabaya. Hasil penelitian menunjukkan bahwa 28% responden memiliki tingkat pengetahuan yang sedang mengenai pendidikan seksual pada anak dengan GSA. Hampir separuh atau 48% responden memiliki tingkat pengetahuan yang baik, dan 15% responden memiliki tingkat pengetahuan yang kurang. Sebagian besar orangtua memiliki pengetahuan yang kurang dalam aspek pengertian seksualitas, tahap perkembangan seksual, dan topik pendidikan seksual yang sesuai dengan usia anak GSA. Kata kunci: pendidikan seksual, pengetahuan orangtua, gangguan spektrum autis